Analyzing E-Commerce Success using DeLone and McLean Model - Ruth Johana Angelina; Aji Hermawan; Arif Imam Suroso (Universitas Airlangga, 2019)
Background: The increasing usage and development of e-commerce in Indonesia, demands competition between e-commerce that exists. To be successful e-commerce should be balanced with a good information system. Some clinical research has established what factors that affected the success, including DeLone and McLean. According to their e-commerce success model, there are six variables that affect e-commerce success, system quality, information quality, service quality, use, user satisfaction, and net benefitObjective: The study aims to analyze the relationship between system quality, information quality and service quality to user satisfaction and use. In addition, the study aims to analyze the relationship between user satisfaction and use to a net benefit.Methods: This study draws on the DeLone and McLean Model of Information System (IS) success model. It is a quantitative study that was conducted in the form of a survey of 110 users of each Lazada, Bukalapak, and Shopee users.Results: By applying DeLone and McLean model, this findings confirmed four hypotheses were significant in Bukalapak, Lazada, and Shopee.Conclusion:There were significant effect between the system quality on user satisfaction, service quality on use, service quality on user satisfaction and user satisfaction on net benefits. Meanwhile, system quality had insignificant effect to use and also information quality to use in Bukalapak, Lazada, and Shopee.Keywords: DeLone and McLean model,E-Commerce Success, Information System Success Measurement, IS Success Model